Simple Three-Input Single-Output Current-Mode Universal Filter Using Single VDCC - Prungsak Uttaphut (Institute of Advanced Engineering and Science, 2018)
This paper presents a second-order current-mode filter with three-inputs and single-output current using single voltage differencing current conveyors (VDCC) along with one resistor and two grounded capacitors. The design of presented filter emphasizes on the use of a single active element without the multiple terminals VDCC which is convenient to implement the VDCC using commercially available IC for the practical test. Also, it can reduce the current tracking error at current output port and can reduce the number of transistor in the VDCC. The proposed filter can realize all the five generic filter responses, namely, band-pass (BP), band-reject (BR), low-pass (LP), high-pass (HP), and all-pass (AP) functions from the same configuration under various conditions in terms of three input current signals. Furthermore, the natural frequency and quality factor are electronically controlled. The output current node exhibits high impedance. Besides, the non-ideal case is also investigated. The simulation and experimental results using VDCC constructed from commercially available IC can validate the theoretical analyses.